PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PBL PADA TOPIK INDUKSI MATEMATIKA KELAS XI MIPA SMA/MA - Randiju Kurniawan (Departemen Matematika, 2020)
This research has a puspose to develop PBL-based learning tools on topic of mathematics induction in class XI MIPA SMA/MA. This design research uses the Plomp development model which comprise of three stages, first the preliminary research, second the development/prototyping phase and last the assessment phase. In the preliminary research, needs analysis, curriculum analysis, concept analysis and student analysis are carried out in order to obtain the main characteristics of the form of the learning tools being developed. In the development/prototyping phase, a prototype design of learning tools was made in the form of PBL-based lesson plans and PBL-based LKPD for mathematics induction material. The prototype must go through formative evaluation in the form of self-evaluation and expert evaluation to obtain a valid prototype. The last stage is the assessment, this assessment aims to determine the practicality criteria of the LKPD prototype which is carried out after the implementation of an one to one evaluation. This research was carried out when Covid-19 was endemic, so there were several stages of research that could not be carried out properly. The conclusion of this study is to obtain PBL-based learning tools on the topic of mathematics induction in the form of lesson plans and student worksheet which are categorized as valid and practical, Keywords — design research, learning tools, PBL, mathematics induction